Effectiveness of MCH handbook development with the addition of fps variables as an early detection for pregnancy and childbirth complications - Citra Dewi Fitri Setiani; Diyah Fatmasari; Ari Suwondo (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: The development of an early detection guidebook for risk factors in pregnant women's complications packaged in MCH books was considered effective for health workers and mothers as guidelines for the prevention of complications. However, the use of MCH books has not been maximal. Of the 81.5% of mothers who own MCH books, only 60.5% understand it. This makes one of the causes of maternal and infant mortality is ignorance of the signs of complications. In addition, in MCH books there is only an assessment of physical disorders without judging from psychological and sociological. Objectives: The purpose of this study was to produce an MCH handbook model with addition NEW FPS (Physiological, Psychological and Sociological) factors to maximize the understanding of pregnant women and the enforcement of high potential risk diagnoses carefully and accurately.Methods: This was Research and Development (R&D) study using Borg and Gall models. The data in the study was obtained using interviews, NEW FPS questionnaires, pregnant women's response trial questionnaires. The population in this study consisted of 16 people and taken a sample of 16 respondents who were pregnant women in trimester 3 to 3 years by using Simple Random Sampling technique.Results: The results showed the development of MCh handbooks with the addition of FPS variabels effectively used as one of the efforts in early detection of pregnancy and childbirth with percentage results: physiological (56.2%) psychological (62.5%) and sociological (68.7%). Based on the results, the response of pregnant women to trials in the development of MCH handbooks obtained an average percentage (87%), the addition of FPS variabels to MCH handbooks was effectively used as an effort to early detection of pregnancy and childbirth complications. The fulfillment of these three aspects can increase the achievement of the MCH program in the early screening of complications.Conclusions: This study concludes that the addition of NEW FPS variabels in MCH handbooks is feasible and effectively used as one of the media to conduct early detection of the occurrence of pregnancy and childbirth.